Changes of Lacrimal Puncta by Anterior Segment Optical Coherence Tomography after Topical Combined Antibiotic and Steroid Treatment in Cases of Inflammatory Punctual Stenosis - Islam Awny; Elshimaa A. Mateen Mossa; Tasneem Mohammed Bakheet; Hany Mahmoud; Amr Mounir (Journal of Ophthalmology)
Purpose. To evaluate the role of medical treatment and assessing its effect on resolving epiphora and improving punctum size by high resolution AS-OCT imaging comparing punctal parameters in patients before and after treatment with topical combined antibiotic and steroid treatment in cases of inflammatory punctual stenosis. Patients and Methods. Double-blinded controlled randomized study which was conducted on two groups of patients who had acquired punctal stenosis and epiphora presented to Ophthalmology Clinics of Sohag University Hospitals in the period between Jan 2021 and April 2021. The study included 44 eyes of 50 subjects complaining of epiphora. They were divided into two groups, the epiphora group one (EG1) received eye drops containing combination of antibiotics and steroids (orchadexoline eye drops, each ml contains 5 mg chloramphenicol, 1 mg dexamethasone sodium phosphate, 0.25 mg tetryzoline hydrochloride, 2 mg hydroxypropyl methyl cellulose, 10 mg α-tocopherol acetate (vitamin E), and 8 mg macrogol 400), 5 times daily for the first week, three times daily for the next two weeks, and one time daily for another one week. The second epiphora group (EG2) received preservative-free artificial tears (sodium hyaluronate-, polyethylene-, and propylene glycol-based), three times daily for four weeks. The patients were examined before treatment, one week, one month, and one and half months later. Results. Both groups were comparable regarding mean age (49 ± 13 vs 53 ± 11 years, P value = 0.2) and sex (males were 38.6% vs 31.8%, female were 61.4% vs 68.2%, P value = 0.6), respectively, with no statistically significant difference between both groups. Both groups were comparable regarding outer punctual diameter and length between the puncti before treatment. Outer punctal diameters were (EG1 228 ± 113 um, EG2 241 ± 115 um, P value = 0.5). Length between the puncti were (EG1 129 ± 73 um, EG2 137 ± 72 um, P value = 0.6). There was marked improvement of the outer punctual diameter (EG1 373 um ± 92 um, EG2 240 ± 109 um, (P value < 0.0001) and length between the puncti (EG1 217 ± 109 um, 136 ± 71 um (P value < 0.0002)) during the follow-up period. EG1 showed more improvement than EG2 when compared during the follow-up period. Conclusions. Topical combined antibiotic and steroid treatment was an effective method in treating cases of inflammatory punctual stenosis as found by monitoring of punctal parameter changes by AS-OCT. AS-OCT was found to be a useful method for evaluation of the lacrimal punctal parameters especially with different treatment modalities in epiphora cases.